Penjajakan Indonesia-Southern African Customs Union Preferential Trade Agreement Dalam Upaya Memperluas Peluang Pasar Non-Tradisional Dan Studi Simulasi Perdagangan Bebas Bilateral RI-Namibia - Sjahril Sabaruddin, Sulthon (Cendekia Niaga, 2022)
This study examines the feasibility of the RI-SACU PTA cooperation in an effort to expand non-traditional market opportunities, especially in the Southern African region. The study illustrated that Southern African region, particularly SACU member countries, is one of the potential regions for alternative trade development, especially for the Indonesian exports. The methodologies used in this study are descriptive approach to describe the economic potentialities, the trade relations development and the level of complementarity of the RI-SACU trade structure, a review of the SACU economic cooperation with third parties, and quantitative approach using the partial equilibrium analysis method with the SMART Model to assess the impact of trade liberalization or free trade on trade, tariff revenue, and welfare effects. Furthermore, TCI results showed that Indonesian exports can better fulfill the import needs of the SACU member countries than vice versa (except South Africa). In an effort to boost the RI-SACU trade performance, the study suggests to establish RI-SACU PTA which is not only will open market access to the SACU region, but also it will make Indonesian products to become more competitive in the SACU market. Furthermore, this study also conducted a free trade simulation between Indonesia and Namibia (one of the member countries of SACU). The simulation uses the SMART Model partial equilibrium analysis method. The RI-Namibia (one of the SACU member states) free trade simulation depicts a very positive impact for Indonesia in which Indonesian exports to Namibia are estimated to increase quite significantly, and at the same time reducing performance of the Indonesian trade competitor countries, particularly South Africa and China, and in the ASEAN context, especially Thailand, Singapore, Malaysia, and Vietnam. In addition, the simulation results also illustrate that trade liberalization between Indonesia and Namibia is predicted to reduce tariff revenues on both countries, and would increase the welfare of consumers from both countries. Furthermore, the challenges experienced and strategies adopted by India, China, and the United States in dealing with the SACU economic cooperation could become a valuable lesson learned for Indonesia pertaining to the RI-SACU PTA cooperation. This paper also suggests ASEAN-SACU PTA and RI-SACU TIDCA could become alternative options to the RI-SACU PTA. Also, it is equally important for the Indonesian government to continue making efforts to enhance Indonesian positive image in the SACU community on the quality and image of Indonesian products, and as well to consider the possibility of establishing production centers in SACU member countries.